The interaction of intense ultrashort laser pulses with cryogenic He planar jets. (23rd February 2017) - Shihab, M; Bornath, Th; Redmer, R
Abstract: We study the interaction of intense ultrashort laser pulses with cryogenic He planar jets, i.e., slabs, using 2D3V relativistic particle-in-cell simulations. Of particular interest are laser intensities ( 10 15 – 10 20 ) W cm −2, pulse lengths ≤100 fs, and the wave length regime ∼800 nm for which the slabs are initially transparent and subsequently inhomogeneously ionized. Pulses ≥ 10 16 W cm −2 are found to drive ionization along the slab and outside the laser spot, the ionization front propagates along the slab at a considerable fraction of the speed of light. Within the ionized region, there is a highly transient field which is a result of the charge-neutralizing disturbance at the slab-vacuum interface and which may be interpreted in terms of a two-surface-wave decay. The ionized region is predicted to reach solid-like densities and temperatures of few to hundreds of eV, i.e., it belongs to warm and hot dense matter regimes. Such extreme conditions are relevant for high-energy densities as found, e.g., in shock-wave experiments and inertial confinement fusion studies. The temporal evolution of the ionization is studied considering theoretically a pump–probe x-ray Thomson scattering scheme. We observe plasmon and non-collective modes that are generated in the slab, and their amplitude is proportional to the ionized volume. Our theoretical findings could be tested at free-electron laser facilities such as FLASH and the European XFEL (Hamburg) and the LCLS (Stanford).